2020
DOI: 10.3390/pr8091187
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of Stability of Vegetable Oils Used as Dielectric Fluids for Electrical Discharge Machining

Abstract: One main drawback of electrical discharge machining (EDM) is related to the dielectric fluid, since it impacts both the environment and operator health and safety. To resolve these issues, recent research has demonstrated the technical feasibility and qualitative performance of vegetable oils as substitutes for hydrocarbon-based dielectric and synthetic oils in EDM. However, due to the higher content of unsaturated fatty acids, vegetable oils lose their stability, due to several factors such as heating or expo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…When machined with other dielectric fluid, MRR reduces with increase in the breakdown strength. 29 Interestingly specimen machined with A2 exhibit high MRR in comparison with C2 composites. In both the cases composites exhibit high MRR than pure alloy.…”
Section: Resultsmentioning
confidence: 94%
“…When machined with other dielectric fluid, MRR reduces with increase in the breakdown strength. 29 Interestingly specimen machined with A2 exhibit high MRR in comparison with C2 composites. In both the cases composites exhibit high MRR than pure alloy.…”
Section: Resultsmentioning
confidence: 94%
“…It is important to keep in mind that these fluids' potential uses are not without their drawbacks. Studies have suggested that deionized water, when used as the dielectric in EDM, increases the corrosion rate of the surface of the implanted material, while carbons released during the combustion of oil-based dielectric fluids react with the alloying elements of the workpiece and the tool electrode to form an extremely hard carbide layer on the substrate [55,60]. Water-based dielectric fluids are predicted to replace oil-based fluids soon, as described by [61,62].…”
Section: Edm's Dielectric Fluidmentioning
confidence: 99%
“…They found that the sunflower oil was resulting similar dielectric properties as that of kerosene but the MRR was increased when sunflower oil was employed as dielectric at same set of input parameters. Radu et al 28 analyzed the variation of physical and chemical properties of different vegetable oils in EDM. Authors had taken soyabean oil and sunflower oil.…”
Section: Introductionmentioning
confidence: 99%